Multicolor TPU / PAN nanofiber yarn and preparation method thereof

Through the blending and electrospinning technology of TPU and PAN, multi-color TPU/PAN nanofiber yarns are prepared, which solves the problems of low yarn strength and the need for base core yarns in the prior art, and achieves excellent hydrophilic and mechanical properties of the yarns, which are suitable for a variety of application fields.

CN119531017APending Publication Date: 2025-02-28ZHEJIANG SCI-TECH UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411712943.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing electrospinning process requires the use of specific substrates as core yarns, and the hydrophilicity and mechanical properties of polyacrylonitrile fibers are poor, making it difficult to meet certain functional and performance needs.

Method used

By blending thermoplastic polyurethane (TPU) with polyacrylonitrile (PAN), and adding cationic dye to the spinning liquid, multi-color TPU/PAN nanofiber yarns are prepared by electrospinning, avoiding the use of substrate as core yarns.

Benefits of technology

The multi-color preparation of yarn is realized, and the hydrophilic and mechanical properties of yarn are improved. It has low cost and less pollution. It is suitable for filtration media and biomedical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of basic fiber materials, and relates to a multicolor TPU / PAN nanofiber yarn and a preparation method thereof. The method comprises the following steps: (1) preparing a TPU / PAN spinning solution; and (2) preparing the multicolor TPU / PAN nanofiber yarn. The preparation method is simple and efficient, the nanofiber yarn is endowed with high-strength low-elasticity mechanical properties and high hydrophilicity, meanwhile, a dye stock solution can be added for coloring, and the multi-color nanofiber yarn is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a multi-color TPU / PAN nanofiber yarn and a preparation method thereof, belonging to the technical field of basic fiber materials. Background Art

[0002] With the rapid development of science and technology, since natural fibers and ordinary chemical fibers cannot meet specific functional and performance requirements, the study of nanofiber materials with various properties has important theoretical significance and application value. As an emerging technology for preparing nanofibers, electrospinning is an important method for preparing ultrafine nanofibers. Electrospinning technology gives electrostatic charges to the surface of nanofibers, which has high research value. Electrostatic charges can give new properties to the surface of nanofibers, making them have excellent characteristics in the fields of tissue engineering, biomedicine, electrode materials, sewage degradation, noise treatment, protective filtration, etc. However, due to the influence of many factors such as spinning process parameters and environmental conditions, the electrospinning process has to use a specific substrate as the core yarn to prepare in order to achieve the continuity of spinning. It has not yet balanced various factors to study and develop a preparation method without core materials. Thermoplastic polyurethane (TPU) is a polymer with strong wear resistance, high tensile strength and elongation at break, low temperature resistance (-35℃ to 50℃) and high temperature resistance (150℃) that has the characteristics of both plastic and rubber.

[0003] Polyacrylonitrile (PAN) is a fiber-forming polymer with a large number of polar groups (cyano groups) in its molecular chain. Its chemical formula is as follows: Figure 1 As shown, it has good electron absorption ability. During the electrostatic spinning process, the electrostatic field can straighten, align and condense the fibers, so that the spinning can be prepared continuously. Therefore, it is widely used as the main spinning body. However, it lacks free hydrophilic groups, the yarn bonding force is poor, resulting in poor mechanical properties of the yarn and low strength of the prepared yarn.

[0004] In addition, environmental pollution caused by dyeing is one of the huge challenges existing in the textile field. This problem can be effectively solved by dyeing the fiber with raw solution, that is, by adding dyes to the spinning solution, spinning and dyeing are integrated, which can effectively improve the coloring uniformity, color fastness and dyeing rate. At the same time, the production cycle is short, the cost is low, and the pollution is less. Summary of the invention

[0005] The object of the present invention is to provide a multi-color TPU / PAN nanofiber yarn, which has excellent hydrophilic properties and has the advantages of simple preparation process, low cost and less pollution.

[0006] Another object of the present invention is to provide a method for preparing the multi-color TPU / PAN nanofiber yarn.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] A method for preparing multi-color TPU / PAN nanofiber yarn, the method comprising the following steps:

[0009] (1) Preparation of TPU / PAN spinning solution

[0010] Mix TPU and PAN with an organic solvent, add a cationic dye, and stir thoroughly to obtain a TPU / PAN spinning solution for electrospinning; the weight ratio of TPU to PAN is 1:2-4;

[0011] (2) Preparation of multi-color TPU / PAN nanofiber yarn

[0012] Under the conditions that the spinning solution flow rate is set to 0.4mL / h-1.0mL / h, the voltage is set to 7-9kV, the twisting speed is set to 120rpm-240rpm, and the collection speed is set to 0.6mm / s-1.0mm / s, the TPU / PAN spinning solution prepared in step (1) is used for electrospinning, and the yarn is used as the core yarn for electrospinning to obtain multi-color TPU / PAN nanofiber yarn.

[0013] Preferably, the cationic dye is 0-4.17wt% based on the total weight of the solute TPU and PAN in the spinning solution as 100wt%. The amount of the cationic dye is selected according to the actual production dyeing needs, but it should not be too much. A high proportion of cationic dye will affect the continuous stability of the spinning process.

[0014] The present invention uses the yarn obtained by electrostatic spinning as the core yarn, and repeatedly spins so that the final yarn product has suitable color, color fastness and mechanical strength. However, since the base material is not used as the core yarn, the influence of factors such as the spinning process on the spinning process needs to be considered. The main purpose of repeated spinning is to make the yarn thicker. At the same time, due to the increase in the number of spinning times, the internal structure of the yarn can be tightened, making the structure more stable and improving the unit breaking strength of the yarn.

[0015] Electrospinning has the advantages of low price, simple equipment, easy operation and high efficiency. It is currently the only effective method for directly and continuously preparing nanofiber yarns. Nanofibers prepared by electrospinning have the advantages of large specific surface area, high porosity, large aspect ratio and good mechanical properties.

[0016] As a fiber-forming polymer, polyacrylonitrile (PAN) has good chemical resistance and dyeing properties. It is widely used as a spinning main body because it contains a large number of polar groups (cyano groups) on its molecular chain, has good electron absorption ability, and has excellent spinnability. However, due to the lack of free hydrophilic groups, polyacrylonitrile fibers have poor hygroscopicity and are prone to static electricity, resulting in poor bonding between fibers, and the strength of the prepared nanofiber yarn is low.

[0017] There are many physical crosslinks formed by hydrogen bonds between linear polyurethane molecular chains, which strengthen their morphology, thus giving TPU many excellent properties, such as high strength, excellent wear resistance, chemical resistance, hydrolysis resistance and high and low temperature resistance. Blending TPU with PAN does not affect the excellent spinnability of PAN nanofiber yarn, while enhancing its strength and hydrophilicity, expanding its application range.

[0018] When the weight ratio of TPU to PAN is too high, the strength of the blended yarn is poor. If it is too high, the polyurethane particles will adhere to the surface of the yarn, and the spinnability of the electrospinning will be reduced. When the weight ratio of TPU to PAN is 1:2-1:4, the mechanical properties and elasticity of the yarn are optimal.

[0019] Preferably, the weight ratio of TPU to PAN is 1:2.

[0020] Preferably, the mass ratio of TPU to cationic dye is 8g:0.1-1g. More preferably, the mass ratio of TPU to cationic dye is 8g:0.5-1g.

[0021] Preferably, in step (1), TPU, PAN, cationic dye and organic solvent are mixed and stirred at 20-80° C. for 2-24 hours to dissolve them in the organic solvent.

[0022] Preferably, in step (1), the organic solvent is DMF, and the usage ratio of TPU, PAN and DMF is 0.8g:1.6g:10.7-26.7g.

[0023] Preferably, the cationic dye in step (1) is cationic yellow X-GL, cationic red X-GRL or cationic blue X-BL.

[0024] Preferably, in step (2), the spinning solution flow rate is 0.6 mL / h, the voltage is 8 kV, the twisting speed is 180 rpm, and the collection speed is 0.6 mm / s. If the collection speed is too slow, the nanofiber cone formed by the fiber on the funnel-shaped collector during electrostatic spinning is unstable, and if the speed is too fast, hairiness will be generated on the fiber surface. As for the voltage, if the voltage is too low, the spinning solution cannot overcome the surface tension and deposit on the funnel-shaped collector, and when the voltage is too high, the excessive electric field strength will cause a large number of nanofibers to fly into the air.

[0025] Preferably, the yarn is used as the core yarn and electrospinning is repeated twice or more, and the yarn diameter is 480 microns to 650 microns.

[0026] A multi-color TPU / PAN nanofiber yarn produced by the preparation method of the present invention.

[0027] The beneficial effects of the present invention are as follows: the present invention first dissolves TPU and PAN particles together to obtain a spinning solution, and then electrospins the TPU / PAN spinning solution to finally obtain a TPU / PAN nanofiber yarn. At the same time, cationic dyes can be added to the spinning solution for electrospinning to obtain multi-color TPU / PAN nanofiber yarns. The nanofiber yarn can be used in filter media, biomedicine and other fields, and has the following characteristics:

[0028] 1. The preparation process of the present invention is simple. Compared with commercial acrylic fiber, spandex requires high-temperature dissolution and melt spinning. Electrospinning consumes less energy and has less pollution to the environment.

[0029] 2. The TPU / PAN nanofiber yarn produced by the invention has excellent hydrophilic properties, and its ultra-high specific surface area can be used in oil-water separation and other aspects;

[0030] 3. The compounding of TPU and PAN will not affect the excellent spinnability of PAN nanofibers. Instead, the obtained product enhances its mechanical properties and greatly improves its strength;

[0031] 4. The addition of cationic dyes enables the preparation of nanofiber yarns in multiple colors, providing technical support for the application research of electrospinning nanofiber yarns.

[0032] The invention realizes a significant improvement in the hydrophilicity and mechanical properties of thermoplastic polyurethane / polyacrylonitrile nanofibers through the application of electrostatic spinning, the preparation of thermoplastic polyurethane and polyacrylonitrile, the selection of spinning technology, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the chemical structural formula of polyacrylonitrile;

[0034] Figure 2 a~2e are SEM morphology images of TPU / PAN nanofibers obtained in Example 1 when the TPU / PAN weight ratio is 0:1, 1:4, 1:2, 1:1, and 3:2;

[0035] Figure 3 To supplement Example 1, the breaking strength (a) and breaking elongation (b) of the TPU / PAN nanofibers obtained when the weight ratio of TPU / PAN was 0:1, 1:4, 1:2, 1:1, and 3:2;

[0036] Figure 4 a~4c are SEM morphology images of electrospun TPU / PAN nanofibers at 120 rpm, 180 rpm, and 240 rpm in Supplementary Example 1;

[0037] Figure 5a~5c are SEM morphology images of electrospun TPU / PAN nanofibers at 7 kV, 8 kV, and 9 kV in Supplementary Example 1;

[0038] Figure 6 a~6e are SEM morphologies of TPU / PAN nanofibers in Supplementary Example 1 after 1 to 5 cycles of electrospinning;

[0039] Figure 7 To supplement Example 1, the elongation at break (a) and unit breaking strength (b) of TPU / PAN nanofibers in the case of electrospinning 1 to 5 times;

[0040] Figure 8 The contact angles of commercial spandex (a), commercial acrylic (b), and TPU / PAN nanofiber yarn (c) of Supplementary Example 2;

[0041] Fig. 9 The wicking heights of commercial spandex (a), commercial acrylic (b), and TPU / PAN nanofiber yarn (c) of Supplementary Example 3;

[0042] Fig.10 This is a physical picture of the multi-color TPU / PAN nanofiber yarn of Example 3;

[0043] Fig.11 The actual picture of the electrospun nanofiber yarn with five different contents of cationic yellow X-GL dye added in Example 3, wherein a, b, c, d, and e correspond to 0.05 g, 0.075 g, 0.1 g, 0.125 g, and 0.15 g of cationic yellow X-GL dye added, respectively;

[0044] Fig.12 The CIE chromaticity diagram of the electrospun nanofiber yarns of Example 3 with 0.05 g, 0.075 g, 0.1 g, 0.125 g, and 0.15 g of cationic yellow X-GL dye added respectively;

[0045] Fig.13 To supplement the color fastness to rubbing of the two dyeing processes using traditional dyeing (a) and solution dyeing (b) in Example 4;

[0046] Fig.14 This is a real picture of a fabric sample made of TPU / PAN nanofiber yarn using a sample loom in Example 4;

[0047] Fig.15 This is the CIE chromaticity diagram of the multi-color nanofiber fabric sample of Example 4;

[0048] Fig.16 Comparison of the color fastness of the fabric samples in Supplementary Example 5 before (a) and after (b) soaping. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0050] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0051] Thermoplastic polyurethane (TPU) was purchased from Hangzhou Mi Ke Chemical Instrument Co., Ltd.;

[0052] Polyacrylonitrile (PAN) was purchased from Hangzhou Mi Ke Chemical Instrument Co., Ltd.;

[0053] N,N-Dimethylformamide (DMF, analytical grade) was purchased from Tianjin Yongda Chemical Reagent;

[0054] Cationic yellow X-GL, cationic red X-GRL and cationic blue X-BL were purchased from Tiancheng Chemical Dye Co., Ltd.

[0055] Example 1

[0056] A method for preparing TPU / PAN nanofiber yarn, the specific steps of the method are as follows:

[0057] (1) Preparation of TPU / PAN spinning solution

[0058] Prepare spinning solutions with weight ratios of TPU to PAN of 0:1, 1:4, 1:2, 1:1, and 3:2, respectively: weigh 0 g, 0.4 g, 0.8 g, 1.6 g, and 2.4 g of TPU particles and 1.6 g of PAN particles, respectively, add them to 18.4 g of DMF solution, and stir magnetically at 80 °C for 3 h to form a uniform spinning solution.

[0059] (2) Preparation of TPU / PAN nanofibers

[0060] The TPU / PAN spinning solution prepared in step (1) was used for electrospinning, and the spinning solution flow rate was set to 0.6 mL / h, the voltage was 7 kV, 8 kV, and 9 kV, the twisting speed was 120 rpm, 180 rpm, and 240 rpm, and the collection speed was 0.6 mm / s. Electrospinning was performed 1 to 5 times, each spinning time was 2 h, and TPU / PAN nanofibers were obtained.

[0061] Supplementary Example 1 Morphology observation and mechanical properties test

[0062] The TPU / PAN nanofibers obtained by electrospinning once with different spinning solution ratios (TPU to PAN weight ratios were 0:1, 1:4, 1:2, 1:1, and 3:2, respectively) were tested:

[0063] The TPU / PAN nanofibers obtained by different spinning solution ratios were observed using an Ultra 55 thermal field emission scanning electron microscope. Figure 2 The mechanical properties of TPU / PAN nanofibers with different spinning solution ratios were tested using an electronic single yarn strength tester. To ensure the accuracy of the results, the test was performed 5 times and the average value was taken. The breaking strength and breaking elongation are shown in Figure 3 As shown. Figure 2 It can be seen that as the spinning solution ratio (TPU / PAN) increases, the fiber diameter will also increase. However, when it reaches the critical ratio and continues to increase, part of the polyurethane will adhere to the fiber surface in the form of particles, increasing the surface roughness, making the fiber structure uneven, and reducing the spinnability of electrospinning. Figure 3 As shown in the figure, when only PAN is used in the spinning solution (the weight ratio of TPU to PAN is 0:1), the breaking strength of the obtained PAN nanofiber is 20cN and the breaking elongation is 5.8%. Due to the poor mechanical properties, the fiber is prone to breakage during the spinning process and cannot be prepared continuously. Figure 3 It can be seen that the strength and elasticity of the yarn are greatly improved after adding polyurethane, but as the concentration of polyurethane continues to increase, the mechanical properties of the yarn decrease. In summary, the spinning solution with a TPU:PAN weight ratio of 1:2 is selected as the optimal parameter.

[0064] The spinning process was investigated by selecting a spinning solution with a weight ratio of TPU:PAN of 1:2. The TPU / PAN nanofibers electrospun under different processes were observed using an Ultra 55 thermal field emission scanning electron microscope. Figure 4 and Figure 5 As shown. If the collection speed is too slow, the fiber cone will be unstable. If the speed is too fast, the fiber surface will produce hairiness. As for the voltage, if the voltage is too low, the spinning solution cannot overcome the surface tension and deposit on the funnel-shaped collector. When the voltage is too high, the electric field strength is too high, causing a large number of nanofibers to fly into the air. In summary, the optimal parameters for the spinning process are 8kV and 180rpm.

[0065] The spinning solution with a weight ratio of TPU:PAN of 1:2 and the spinning process parameters of 8kV and 180rpm were selected for the investigation of electrospinning times: the TPU / PAN nanofibers after different spinning times were observed using an Ultra 55 thermal field emission scanning electron microscope. The electron microscope photos are shown in Figure 6The mechanical properties of TPU / PAN nanofibers with different spinning times were tested using an electronic single yarn strength tester. To ensure the accuracy of the results, the test was performed 5 times and the average value was taken. The elongation at break, breaking strength and unit breaking strength are shown in Figure 7 As shown in the figure, with the increase of spinning times, the fiber diameter increases, the elongation at break increases slightly, and the unit breaking strength remains basically unchanged after the spinning times exceed 3 times. This is because in the first few spinning times, the fiber structure is not completely arranged, and with the increase of spinning times, the fiber structure is improved and becomes more uniform, and at the same time the fibers become closer, making the yarn structure relatively stable.

[0066] Comparative Example 1

[0067] A method for preparing TPU nanofiber yarn, the specific steps of the method are as follows:

[0068] (1) Preparation of TPU spinning solution

[0069] 0.8 g of TPU particles were weighed and added to 2.4 g of DMF solution, and magnetically stirred at 80° C. for 3 h to form a uniform spinning solution.

[0070] (2) Preparation of TPU nanofibers

[0071] The TPU spinning solution prepared in step (1) was used for electrospinning. The spinning solution flow rate was set to 0.6 mL / h, the voltage was 8 kV, the twisting speed was 180 rpm, and the collection speed was 0.6 mm / s. The electrospinning was performed for 2 h to obtain TPU nanofibers.

[0072] During the spinning process, due to the large elastic force of TPU nano yarn, the fiber cone formed by the jet generated by the syringe in the funnel-shaped collector is too thick, resulting in the inability to twist normally to form nanofiber bundles. The TPU nano yarn is prone to breakage and cannot be prepared continuously.

[0073] Example 2

[0074] A method for preparing TPU / PAN nanofiber yarn, the specific steps of the method are as follows:

[0075] (1) Preparation of TPU / PAN spinning solution

[0076] 0.8 g of TPU particles and 1.6 g of PAN particles were weighed, added to 18.4 g of DMF solution, and magnetically stirred at 80° C. for 3 h to form a uniform spinning solution.

[0077] (2) Preparation of TPU / PAN nanofibers

[0078] The TPU / PAN spinning solution prepared in step (1) was used for electrospinning. The spinning solution flow rate was set to 0.6 mL / h, the voltage was 8 kV, the twisting speed was 180 rpm, and the collection speed was 0.6 mm / s. The electrospinning was performed for 2 h to obtain TPU / PAN nanofibers.

[0079] Supplementary Example 2 Contact Angle Test

[0080] In order to measure the contact angle of TPU / PAN nanofibers, the water contact angles of TPU / PAN nanofibers, commercial spandex and commercial acrylic were measured by a video contact angle tensiometer, and their hydrophilicity was compared by the contact angles of the three. The results are shown in the figure. Figure 8 It can be seen that since both commercial spandex and commercial acrylic have been surface treated, their contact angles are relatively large, spandex contact angle is 110.2°, acrylic contact angle is 75.6°, and both have poor hydrophilicity. However, nanofibers have ultra-high specific surface area, and the polar groups in TPU and PAN make the prepared blended yarn have a relatively small contact angle of 28.6°, which has good hydrophilicity.

[0081] Supplementary Example 3 Hydrophilicity Analysis

[0082] In order to measure the liquid carrying rate of TPU / PAN nanofibers, five yarn samples of TPU / PAN nanofibers, commercial spandex and commercial acrylic were adjusted to balance under constant temperature and humidity conditions, and the original mass of the sample was weighed and recorded by an electronic balance. Then the sample was placed in a container filled with three-level water, and after soaking the sample, it was naturally suspended vertically and flatly as required until the dripping gap of the yarn on the sample was less than 30s, and then the sample mass was taken down, weighed and recorded. The liquid carrying rate was calculated by comparing the mass before and after soaking, and the hydrophilicity was compared by the liquid carrying rates of the three. Since both commercial spandex and commercial acrylic have been surface treated, the liquid carrying rates of the two are low, the liquid carrying rate of spandex is 48.6%, and the liquid carrying rate of acrylic is 254.3%, and the hydrophilicity of the two is poor. The ultra-high specific surface area of ​​nanofibers, and the polar groups in TPU and PAN make the prepared blended yarn have a large liquid carrying rate of 489.2%, which has good hydrophilicity.

[0083] In order to measure the wicking height of the capillary effect of TPU / PAN nanofibers, 25 20 cm yarns of TPU / PAN nanofibers, commercial spandex and commercial acrylic were tightly wound into ropes, and the yarns were kept in a naturally straight state. The lower ends were immersed in liquid (the liquid contained 1% dye for easy observation). After 30 minutes, the wicking heights of commercial spandex, TPU / PAN nanofibers and commercial acrylic were observed. Fig. 9The hydrophilicity of the three was compared by the wicking height. Since both commercial spandex and commercial acrylic have been surface treated, their wicking heights are relatively low, with spandex wicking height of 13cm and acrylic wicking height of 0.5cm. The hydrophilicity of the two is relatively poor. The ultra-high specific surface area of ​​nanofibers, as well as the polar groups in TPU and PAN, make the prepared blended yarn wicking height higher, reaching 18cm, and has good hydrophilicity.

[0084] Example 3 Investigating the effect of dye addition on spinning effect

[0085] A method for preparing multi-color TPU / PAN nanofiber yarn, the specific steps of the method are as follows:

[0086] (1) Preparation of TPU / PAN spinning solution

[0087] 0.8 g of TPU particles and 1.6 g of PAN particles were weighed and added to 18.4 g of DMF solution, and then different weights of cationic yellow X-GL dye were added, and magnetic stirring was performed at 80° C. for 3 h to form a uniform spinning solution.

[0088] The added amounts of cationic yellow X-GL dye are 0.05g, 0.075g, 0.1g, 0.125g and 0.15g respectively.

[0089] (2) Preparation of multi-color TPU / PAN nanofibers

[0090] The TPU / PAN spinning solution prepared in step (1) was used for electrospinning. The spinning solution flow rate was set to 0.6 mL / h, the voltage was 8 kV, the twisting speed was 180 rpm, and the collection speed was 0.6 mm / s. The electrospinning was performed for 2 h to obtain TPU / PAN nanofibers.

[0091] When the mass ratio of TPU and cationic dye is 0.8g:0.05g, the multi-color TPU / PAN nanofiber yarn is obtained. Fig.10 As shown, the overall fineness of the yarn is uniform, there is no excess hair on the surface, the cationic yellow X-GL dye is well combined with the yarn, and the color is uniform.

[0092] Photos of yarns obtained by spinning with different weights of cationic yellow X-GL dye are shown below. Fig.11 As shown, Fig.11 In the figure, a, b, c, d, and e correspond to yarns made with 0.05 g, 0.075 g, 0.1 g, 0.125 g, and 0.15 g of cationic yellow X-GL dye added, respectively. Fig.11 a and Fig.10The same as the yarn. As the dye content increases, the color of the prepared yarn gradually deepens. When the cationic dye addition amount is 0.1g, the yarn color is the darkest; when the cationic dye addition amount exceeds 0.1g, the yarn color becomes lighter. CIE diagram Fig.12 As shown, it can be seen that as the content increases, the coordinates in the CIE diagram shift toward the edge, which indicates that the color gradually deepens. When the amount of cationic yellow X-GL dye added is 0.125g and 0.15g, the CIE coordinates are farther away from the edge than the coordinates of the dye addition amount of 0.1g, indicating that the color becomes lighter. This is because the cationic dye increases the conductivity of spinning in the spinning solution, reduces the charge aggregation effect, and destroys the stability of spinning. At the same time, the residual dye will gather at the needle head and drip in the form of droplets. The increase of cationic dye in the spinning solution affects the spinning effect. Therefore, in the spinning solution, when TPU is 0.8g, it is appropriate that the amount of cationic dye added does not exceed 0.1g. In order to maintain the continuous stability of the spinning process, the appropriate range of dye in the spinning solution is 0-4.17wt%, based on the total weight of solute TPU and PAN in the spinning solution as 100wt%.

[0093] Comparative Example 3: Traditional dyeing of dyed yarn

[0094] (1) Preparation of TPU / PAN spinning solution

[0095] As in Example 2;

[0096] (2) Preparation of TPU / PAN nanofiber yarn

[0097] As in Example 2;

[0098] (3) Preparation of traditional dyeing solution

[0099] Weigh 0.002 g of cationic yellow X-GL dye, 0.002 g of acetic acid, 0.001 g of sodium carbonate, and 0.0005 g of sodium sulfate, add them into 100 g of deionized water, and stir them magnetically at room temperature for 1 h to form a uniform dye solution.

[0100] (4) Preparation of traditional dyed yarn

[0101] Take 1 g of the TPU / PAN nanofiber yarn prepared in step (2), raise the temperature from 75°C to 95°C at a rate of 1°C / min and maintain for 60 minutes. After dyeing, rinse in cold water and dry to obtain traditional dyed yarn.

[0102] Supplementary Example 4 Analysis of Color Fastness to Rubbing

[0103] In order to test the color fastness to rubbing of multi-color TPU / PAN nanofibers, dyes were dyed onto blended yarns using the traditional dyeing process, and the color fastness to rubbing was tested together with the solution-dyed blended yarns. The results are shown in Figure 2. Fig.13 As shown in the figure, both the solution-dyed yarn and the yarn prepared by traditional dyeing have high color fastness to rubbing, the cloth sample on the friction head is basically not stained, the degree of colored yarn transferred to the friction white cloth through friction is low, and the color fastness to rubbing can reach level 4-5.

[0104] In the traditional dyeing method, spandex needs to be dissolved and melt-spun at high temperature, and the yarn needs to be soaked in additional dye solution for dyeing, which is labor-intensive, water-intensive and energy-intensive. However, the present invention can prepare colored yarns through electrostatic spinning, which consumes less energy and has little pollution to the environment.

[0105] Example 4

[0106] A method for preparing a multi-color TPU / PAN nanofiber fabric sample, the specific steps of the method are as follows:

[0107] (1) Preparation of TPU / PAN spinning solution

[0108] Weigh 0.8 g of TPU particles and 1.6 g of PAN particles, add them to 18.4 g of DMF solution, then add 0.05 g of cationic yellow X-GL, cationic red X-GRL, and cationic blue X-BL dyes, and stir magnetically at 80°C for 3 h to form a uniform spinning solution.

[0109] (2) Preparation of TPU / PAN nanofibers

[0110] The TPU / PAN spinning solution prepared in step (1) was used for electrospinning. The spinning solution flow rate was set to 0.6 mL / h, the voltage was 8 kV, the twisting speed was 180 rpm, and the collection speed was 0.6 mm / s. The electrospinning was performed for 2 h to obtain TPU / PAN nanofibers.

[0111] (3) Fabric sample preparation

[0112] The obtained TPU / PAN nanofiber yarn is woven into a fabric sample using a sample loom. The obtained multi-color TPU / PAN nanofiber fabric sample is as shown in FIG. Fig.14 As shown in a, b, and c, the whole piece of fabric is tightly combined and smooth. Fig.15 .

[0113] Supplementary Example 5: Analysis of Color Fastness to Soaping

[0114] In order to test the soap color fastness of multi-color TPU / PAN nanofibers, the multi-color TPU / PAN nanofibers were tested for their soap color fastness by a washing color fastness instrument. The results are as follows Fig.16 As shown. The stronger the binding force between the dye and the fiber, the more fully the dye diffuses during the dyeing process, and the better the soap fastness. The cyano group in polyacrylonitrile, the isocyanate group in polyurethane, and the amide group have higher electronegativity, which can produce stronger adsorption with cationic yellow dyes. As can be seen from the figure, the soap solution of TPU / PAN blended fabric treated with soaping for 30min / 40℃ has a slight floating color, and the color of the fabric sample does not change much. Its color fastness is about 4 to 5 levels, which can meet the industry standard.

[0115] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0116] The above is a detailed introduction to a multi-color TPU / PAN nanofiber yarn and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing multi-color TPU / PAN nanofiber yarn, characterized in that The method comprises the following steps: (1) Preparation of TPU / PAN spinning solution Mix TPU and PAN with an organic solvent, add a cationic dye, and stir thoroughly to obtain a TPU / PAN spinning solution for electrospinning; the weight ratio of TPU to PAN is 1:2-4; (2) Preparation of multi-color TPU / PAN nanofiber yarn Under the conditions that the spinning solution flow rate is set to 0.4mL / h-1.0mL / h, the voltage is set to 7-9kV, the twisting speed is set to 120rpm-240rpm, and the collection speed is set to 0.6mm / s-1.0mm / s, the TPU / PAN spinning solution prepared in step (1) is used for electrospinning, and the yarn is used as the core yarn for electrospinning to obtain multi-color TPU / PAN nanofiber yarn.

2. The preparation method according to claim 1, characterized in that: The weight ratio of TPU to PAN is 1:

2.

3. The preparation method according to claim 1, characterized in that: The mass ratio of TPU to cationic dye is 8g:0.1-1g.

4. The preparation method according to claim 1, characterized in that: The mass ratio of TPU to cationic dye is 8g:0.5-1g.

5. The preparation method according to claim 1, characterized in that: In step (1), TPU, PAN, cationic dye and organic solvent are mixed and then stirred at 20-80° C. for 2-24 hours to dissolve them in the organic solvent.

6. The preparation method according to claim 1, characterized in that: In step (1), the organic solvent is DMF, and the usage ratio of TPU, PAN and DMF is 0.8g:1.6g:10.7-26.7g.

7. The preparation method according to claim 1, characterized in that: The cationic dye in step (1) is cationic yellow X-GL, cationic red X-GRL or cationic blue X-BL.

8. The preparation method according to claim 1, characterized in that: In step (2), the spinning solution flow rate is 0.6 mL / h, the voltage is 8 kV, the twisting speed is 180 rpm, and the collection speed is 0.6 mm / s.

9. The preparation method according to claim 1, characterized in that: In step (2), the yarn is used as the core yarn and the electrostatic spinning is repeated twice or more, and the yarn diameter is 480 microns to 650 microns.

10. A multi-color TPU / PAN nanofiber yarn produced by the preparation method according to claim 1.

Citation Information

Patent Citations

  • dyeing and printing of shaped structures made of polyacrylonitrile and polyacrylonitrile-containing copolymers

    AT208808B

  • Continuous preparation method for ultra-fine electrostatic spinning fibre yarn

    CN101104970A

  • A preparation method for color nanofiber yarns

    CN106120157A

  • Functional yarn preparation method

    CN113969446A

  • Preparation method of cotton fiber / thermoplastic polyurethane nanofiber blended yarn

    CN114318603A